Two outbreaks of SARS-CoV-2 in department of surgery in a Wuhan hospital - Shicheng Gao; Yufeng Yuan; Yong Xiong; Yongxi Zhang; Liping Deng; Tielong Chen; Hengning Ke; Xinghuan Wang (Elsevier, 2020)
Summary: The outbreak of SARS-CoV-2 in China, attracted a large number of medical staff to help in the city's hospitals and this put them at a high risk of infection. We describe twenty medical staff who were diagnosed with COVID-19 within one week in the department of surgery in a Wuhan hospital. Epidemiological investigation of these cases identified misdiagnosed patients (source of infection), an inappropriate clinical meeting and working without wearing face masks to be the causes of the outbreaks. This report emphasizes the importance of wearing a facemask and applying other standard infection control precautions to protect medical personnel from infection with the virus.